Usability Analysis of the Authentication Feature in the Andal by Taspen Application Using the System Usability Scale Method - Sari, Putri Permata; Kholil, Ishak (Asosiasi Dosen Muda Indonesia, 2026)
This study evaluates the usability of the authentication feature in the Andal by Taspen application for pensioners, focusing on challenges faced by elderly users, as initial reviews indicate issues with its effectiveness. Objective: This study aims to assess the usability of the Andal by Taspen authentication feature using the System Usability Scale (SUS) method, identify usability issues affecting elderly users, and provide recommendations for improvement. Specifically, the study focuses on evaluating whether the selfie-based authentication process meets the needs of elderly pensioners, who may face challenges in digital literacy and physical limitations. Methodology: This quantitative study involved distributing the System Usability Scale (SUS) questionnaire to PT Taspen pensioners in the Cempaka Putih District, Jakarta. The responses were analyzed using the SUS method to generate a usability score for the authentication feature and to identify areas for improvement. Findings: The findings reveal that the Andal by Taspen authentication feature received a SUS score of 61, which corresponds to Grade D on the SUS scale, with an adjective rating of